Coefficient Bounds of Kamali-Type Starlike Functions Related with a Limacon-Shaped Domain - Gangadharan Murugusundaramoorthy; Ayesha Shakeel; Marwan Amin Kutbi (Journal of Function Spaces)
In this article, we familiarize a subclass of Kamali-type starlike functions connected with limacon domain of bean shape. We examine certain initial coefficient bounds and Fekete-Szegö inequalities for the functions in this class. Analogous results have been acquired for the functions f−1 and ξ/fξ and also found the upper bound for the second Hankel determinant a2a4−a32.